A cross-sectional study to assess job strain of emergency healthcare workers by Karasek questionnaire: The SEEK study - Bouillon-Minois, Jean-Baptiste; Trousselard, Marion; Mulliez, Aurélien; Adeyemi, Oluwaseun John; Schmidt, Jeannot; Thivel, David; Ugbolue, Ukadike Chris; Borel, Marjolaine; Moustafa, Farès; Vallet, Guillaume T.; Clinchamps, Maëlys; Zak, Marek; et al. (Frontiers in Psychiatry, 2023)
Background Emergency healthcare workers (eHCWs) are particularly at risk of stress, but data using the gold standard questionnaire of Karasek are scarce. We assessed the level of stress of eHCWs and aimed to compare it with the general population. Methods This is a cross-sectional nationwide study in French Emergency Departments (EDs), using the job-content questionnaire of Karasek, compared with the 25,000 answers in the French general population (controls from the SUMER study). The descriptions of job demand, job control, and social support were described as well as the prevalence of job strain and isostrain. Putative factors were searched using mixed-method analysis. Results A total of 166 eHCWs (37.9 ± 10.5 years old, 42% men) from five French EDs were included: 53 emergency physicians and 104 emergency paramedics, compared to 25,000 workers with other occupations. Job demand was highest for physicians (28.3 ± 3.3) and paramedics (25.9 ± 3.8), compared to controls (36.0 ± 7.2; p < 0.001). Job control was the lowest for physicians (61.2 ± 5.8) and paramedics (59.1 ± 6.8), compared to controls (70.4 ± 11.7; p < 0.001). Mean social support did not differ between groups (23.6 ± 3.4 for physicians, 22.6 ± 2.9 for paramedics, and 23.7 ± 3.6 for controls). The prevalence of job strain was massively higher for physicians (95.8%) and paramedics (84.8%), compared to controls (23.9%; p < 0.001), as well as for isostrain (45.1% for physicians, 56.8% for paramedics, and 14.3% for controls, p < 0.001). We did not find any significant impact of sociodemographic characteristics on job control, job demand, or social support. Conclusion Emergency healthcare workers have a dramatic rate of job strain, necessitating urgent promotion of policy to take care of them.